Synthesis and characterization of heterobenzenacyclo-octaphanes derived from cyclotetrabenzoin - Hahn, Sebastian; Sontheim, Anna; Rominger, Frank; Bunz, Uwe H. F. (Chemistry - a European journal, 2017)
We describe the modular synthesis and characterization of several substituted N-hetero benzenacyclooctaphanes (BAOs), a new motif for heteroaromatic conjugated macrocycles. The targets were synthesized via condensation of substituted aromatic ortho-diamines with a cyclic octaketone building block in moderate to excellent yields (41-91 %). We evaluated the optical and electronic properties and the solid-state structures of the targets and discuss their properties through comparison with their linear diphenyl N-heteroacene counterparts.
Gesehen am 07.05.2018